Michalis Karambinis. The island of Skyros from Late Roman to Early Modern times - Intagliata, Emanuele E. (Journal of Greek Archaeology, 2017)
The island of Skyros presents the results of a PhD research project conducted at Leiden University by M. Karambinis, a native of Skyros, who worked for the Archaeological Ephorate of Euboea from 2007 to 2015. It offers a comprehensive overview of the history and archaeology of Skyros from Late Roman to early modern time. The work integrates data retrieved from past archaeological works, new intensive and extensive surveys of the island and historical sources. This all-encompassing approach to the archaeological and historical record of the island means that more unusual materials for the archaeologist, such as Ottoman costumes and furniture, are also included in Karambinis’ analysis. The book is divided into four Parts: 1. Background and historical data, 2. The archaeological survey: methodology and comparisons, 3. The archaeological survey: the sites, and 4. Interpretational synthesis. It also includes four appendices, namely: A. Gazeteer of archaeological sites, B. Catalogue of pottery, C. Catalogue of churches (Chora and suburbs), D. The synoptic Ottoman tax register (icmal) of the year 1670/1 for Skyros. It concludes with a bibliography, a summary in Dutch and notes about the authors. In total, this rather voluminous book includes 13 chapters and an introduction.